a) Sin²α - 1 = - (1 - Sin²α) = - Cos²α
Это следует из первого тригонометрического тождества :
Sin²α + Cos²α = 1
б)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
a) Sin²α - 1 = - (1 - Sin²α) = - Cos²α
Это следует из первого тригонометрического тождества :
Sin²α + Cos²α = 1
б)![Cos^{2}\alpha+Sin^{2} \alpha+Ctg^{2}\alpha=1+Ctg^{2} \alpha=\frac{1}{Sin^{2}\alpha} Cos^{2}\alpha+Sin^{2} \alpha+Ctg^{2}\alpha=1+Ctg^{2} \alpha=\frac{1}{Sin^{2}\alpha}](https://tex.z-dn.net/?f=Cos%5E%7B2%7D%5Calpha%2BSin%5E%7B2%7D%20%5Calpha%2BCtg%5E%7B2%7D%5Calpha%3D1%2BCtg%5E%7B2%7D%20%5Calpha%3D%5Cfrac%7B1%7D%7BSin%5E%7B2%7D%5Calpha%7D)